2014
DOI: 10.1007/s13197-014-1560-y
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Lactobacillus adjuncts culture to improve the quality of Feta-type cheese made using buffalo milk

Abstract: Feta-type cheese was made from buffalo milk using commercial adjunct culture of Lactobacillus helveticus and Lactobacillus casei along with standard mesophillic cheese cultures. The sensory, biochemical and texture characteristics of the experimental cheeses were studied during ripening. Expert panellists observed, significant differences (P<0.01) between the control and the experimental cheeses. The pH, titratable acidity, soluble protein and free fatty acid content of the experimental cheeses were found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
(23 reference statements)
4
6
0
Order By: Relevance
“…However, the color scores were reduced in all treatments during the 14 days of storage and this could be due to the loss of moisture during the ripening. A similar trend has been found in Feta cheese when it was stored for 60 days (Kumar et al., 2015). Also, other researchers noticed that the color of full‐fat and LFC was decreased during storage for 180 days (Katsiari et al., 2002) which is similar to our results.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…However, the color scores were reduced in all treatments during the 14 days of storage and this could be due to the loss of moisture during the ripening. A similar trend has been found in Feta cheese when it was stored for 60 days (Kumar et al., 2015). Also, other researchers noticed that the color of full‐fat and LFC was decreased during storage for 180 days (Katsiari et al., 2002) which is similar to our results.…”
Section: Resultssupporting
confidence: 83%
“…It has been reported that LFC (7% fat) did not show any differences with full‐fat Feta cheese with 22% fat when adjunct cultures were utilized (Katsiari et al., 2002). A correlative trend was found in another study when Feta cheese was manufactured using adjunct cultures (Kumar et al., 2015). Another study reported that adjunct cultures improved low‐fat Cheddar cheese (Banks et al., 1993).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Since lactobacilli have been commonly used as adjunct cultures for enhancing the sensory quality of different cheeses (Ciocia, McSweeney, Piraino, & Parente, 2013;Kumar, Kanawjia, & Kumar, 2015), the levels of key volatiles produced in milk by wild Lc. lactis were compared with those of four selected strains of Lactobacillus (Table 1).…”
Section: Analysis Of Volatile Compounds In Fermented Milk and Cheesementioning
confidence: 99%
“…In this experiment, the addition of L. paracasei LPC-37 as the adjunct culture contributed to an increase in the content of butyric, isovaleric, valeric and caproic acid in experimental cheeses (Table 2). An increase in the extent of lipolysis in cheeses containing additional cultures, including Lactobacillus, has been demonstrated in numerous studies (Kumar et al, 2015;Hynes et al, 2002;Madkor et al, 1999). It should be noted, however, that bacterial cultures and strains have different lipolytic activity (Madkor et al, 1999).…”
Section: Resultsmentioning
confidence: 85%